The Quotative in Bashkir - Teija Greed (Studia Orientalia Electronica, 2018)
Evidentiality is a widely researched category in contemporary linguistics, both from the viewpoint of grammatical expression and also that of semantics/pragmatics. Amongst markers expressing information source is the illocutionary evidential quotative, which codes a speech report with an explicit reference to the quoted source. This article investigates the quotative particle tip in Bashkir, a Kipchak-Bulgar Turkic language spoken in the Russian Federation. In its default quotative meaning, tip signals direct speech and functions as a syntactic complementiser. This function was found to have extended from spoken utterances to coding thoughts and experiences in the context of semi-direct speech. A separate function of tip is its use as an adverbialiser signalling a logical relation and conveying the meaning of intention/purpose. Different categories were found to interact in the functions of tip. In the context of semi-direct speech, the meaning tip conveys is linked with the semantic dimension of subjectivity, which pertains to the cognitive processing and expressing of information by the speaker/experiencer. The interplay of the marker tip was investigated in conjunction with ten complement-taking verbs, whose degree and strength of subjectivity were found to range from neutral to strong. When combined with küreü ‘see’, tip introduces visual ambiguity and epistemic uncertainty, for example, in dream scenes. With the verbs beleü ‘know’ and išeteü ‘hear’, tip conveys a multisubjective meaning: in addition to signalling what the experiential subject has heard or found out, the marker also codes the involvement of some other subject, the original source, thus giving voice to multiple speakers and merging them.